Barriers to the profession: inaction in Ontario, Canada and its consequences - Levin, Avner (Oñati Socio-Legal Series, 2013)
The province of Ontario, Canada, has not had a new law school in almost 40 years. Barriers limiting access to the profession have increased during this time due to a combination of factors discussed in this paper. Diversity within the legal profession has not improved, leading to the perception of a profession dominated by “old white males” whose services are increasingly unaffordable. The paper argues that barriers should be removed and that access to the profession should be greatly increased.